PENINGKATAN KETERAMPILAN MEMBACA LANCAR MELALUI PERMAINAN SCRAMBLE PADA PESERTA DIDIK KELAS II DI SD INPRES BERTINGKAT OEBA 5 KOTA KUPANG - Sampe, Markus; Koro, Maxsel; Mokoni, Jecky Lani (Universitas Nusa Cendana, 2024)
The purpose of this study is to improve the reading fluency skills of second-grade students at SD Inpres Bertingkat Oeba 5 Kota Kupang through the game of scramble. The research method used is classroom action research (PTK) conducted through a collaborative process between the researcher and the class teacher, as well as the research subjects, which are 37 second-grade students SD Inpres Bertingkat Oeba 5 Kota Kupang, consisting of 14 male students and 23 female students. The researcher used observation, interviews, reading fluency skill tests, and documentation techniques to collect data. The data analysis technique used in this study is descriptive qualitative analysis, which seeks to find the percentage of collected data and then classify it according to predetermined formulas. The results of this study show that in the pre-cycle the classical average score was 53.91 with a completion percentage of 21.62% (8 students completed it) increasing in cycle I with a classical average score of 73.37 with a completion percentage of 54.04% (20 students completed) then increased in cycle II with an average score of 92.02 with a completion percentage of 95.59% (35 students completed) thus the use of the scramble game can improve the fluent reading skills of class II students at SD Inpres Bertingkat Oeba 5 Kota Kupang.